TEACHING SPEAKING BY USING ROLE PLAY TO THE EIGHTH GRADERS OF STATE JUNIOR HIGH SCHOOL 15 PALEMBANG - Jhoni Eppendi (JAMBI-ENGLISH LANGUAGE TEACHING, 2016)
English speaking skill is one of skills to be noticed in this globalization era. However, Indonesian English speaking skill was still low. Therefore, the objective of this study was to find out whether or not the use of Role Play strategy could improve students’ speaking performance. 60 out of 212 eighth graders of State Junior High School 15 Palembang were chosen randomly as the sample. In collecting the data, the pre-test and post-test were given to both groups to measure their speaking skill. The result showed that speaking achievement of the students who are taught by using role play were significantly improve those who were not. Role play could motivate and attract their attention to the lesson. They were active in expressing their ideas, feelings and opinions freely. The students like role play because it is like a game. Thus, the students enjoy to be active orally especially for shy students. It means that role play is effective to be used in teaching speaking to the Eighth Graders of State Junior High School 15 Palembang.